The Effect of Learning Independence, Self-Regulation, and Social Support on Learning Achievement among Psychology Department Students X University in Covid-19 Pandemic Era - Cicilia Emita; Samuel Lukas (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2022)
During the Covid-19 pandemic, the Indonesian Government issued a policy to implement Distance Learning (PJJ) or Online Learning. This applies to all levels of education, including higher education. During online learning, students are not only required to have learning independence but also self-regulation and social support to meet the expected learning outcomes. This study aims to analyze the effect of learning independence, self-regulation, and social support on students’ learning outcomes. The subjects of this study were 115 students from the Psychology Study Program at University X. The research design used was multiple regression with a quantitative approach. A questionnaire was used as the research instrument. The validity and reliability of the measuring instrument used were adequately credible. The classical assumption test was conducted in the form of a normality test, homogeneity test, and correlation test before the hypothesis testing was carried out with regression testing. Partially, each independent variable independently affects the dependent variable. Learning independence affects Learning Outcomes with a significance value of 0.448, self-regulation also affects Learning Outcomes with a significance value of 0.551, and social support also affects Learning Outcomes with a significance value of 0.104. The three independent variables, namely Learning Independence, Self-Regulation, and Social Support, jointly affect the dependent variable on Learning Outcomes with a significance value of 0,527.